Emergency water supply and water resources management in Tongzhou District, Nantong City, China. Issue 3 (4th May 2017) - Zhang, Xiu-Ju; Ding, Kai-Sen; Hao, Meng-ru; Long, Mei
Abstract: Water resources emergency management can mitigate regional damage from water emergencies. Taking Tongzhou District, Nantong City as the study area, this paper proposes technical and engineering measures to improve the water emergency management system. This paper chooses groundwater as the alternative emergency water source, and proposes an emergency wells layout scheme according to the disparities between current groundwater supply capacities and the emergency water demands in each planning unit in 2020. Jiuweigang River and Tonglv River are proposed as water-dilution channels to improve the surface water environment and provide suitable water to Tongzhou District by means of sluice gates. Lastly, this paper describes the water resources emergency management mechanism, including the organization system, the response mechanism, and the supporting measures.